Effect of non-genetic factors and genetic parameter estimation of reproductive traits in Malpura sheep - Govind Mohan; GR Gowane; Arun Kumar; AK Chakravarty (Journal of Livestock Biodiversity, 2025)
Malpura sheep is a heavy and well adapted breed of the semi-arid region of India. A total of 609 Malpura sheep, over a period of 10 years (1994 to 2003) at ICAR-CSWRI Avikanagar were studied. The least squares mean value of AFS, AFSS, WFS, WFSS and AFL for the Malpura ewes was obtained as 598.14 ± 8.43 days, 664.81 ± 13.42 days , 26.18 ± 0.19 kg, 27.08 ± 0.21 kg and 816.54 ± 13.45 days, respectively. Highly significant effect of year was observed on all these reproduction traits, whereas, lambing season of ewes was not significantly affecting all these traits. The heritability of reproductive traits viz., AFS, AFSS, AFL, WFS, WFSS and WFL were estimated as 0.15 ± 0.09, 0.19 ± 0.10, 0.18 ± 0.09, 0.34 ± 0.10, 0.20 ± 0.10and 0.16 ± 0.10 respectively. The heritability estimates were signiicant and with moderate values, which will be helpful in selective breeding of the animals for these traits.